Prediction value of creatine kinase level in conservative treated unruptured tubal ectopic pregnancies - Rahımlı Ocakoglu, Sakine; Develioğlu, Osman Haldun (The European Research Journal, 2021)
Objectives: An ectopic pregnancy (EP) occurs when a fertilized ovum implants outside the endometrial cavity. We investigated the creatine kinase (CK) enzyme in conservatively treated EP to determine the resolution time and predict cases that may progress to surgical intervention. Methods: We include 43 patients with stable vital signs at recruitment. All participants were examined by using transvaginal ultrasound (TVUS). Beta human chorionic gonadotropin (β-hCG) and creatine kinase (CK) levels were also measured. In cases diagnosed with EP, intramuscular methotrexate (MTX) at a dose of 50 mg / m2 was administered and monitored with β-hCG titers. Follow-up continued until β-hCG titer became negative, or surgery became mandatory due to acute abdominal pain. Results: The mean β-hCG Level in the presence of an adnexal mass was statistically significantly higher than the mean level in patients in whom TVUS failed to define a mass. The mean β-hCG level in the surgical exploration group of patients was significantly higher than in those who did not require surgery. At a cut-off of 6486 mIU/mL, β-hCG could predict the emergence of acute abdomen with a sensitivity of 75% and a specificity of 94.3%. We examined CK level to contribute the test’s specificity, but we found no difference among cases with and without surgical exploration. Conclusions: In patients treated conservatively for EP, CK levels at the outset neither predict an acute abdomen to emerge nor shed light on the resolution period in patients who respond to medical therapy.